2020
DOI: 10.1590/2318-0331.252020190093
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for physical modeling of reservoir sedimentation

Abstract: RESUMO Reservatórios construídos em cursos d’água estão sujeitos a algum grau de assoreamento. Por isso, é importante a estimativa do volume de sedimentos acumulados, visto que esse depósito pode interferir nas funções do reservatório. Uma forma de se fazer isso é utilizando modelos físicos. Entretanto, a partir da literatura existente na área não é possível responder a algumas questões metodológicas que surgem em uma simulação física do assoreamento, como: qual vazão e descarga sólida utilizar? Simular um hid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
1
5
0
3
Order By: Relevance
“…Aiming at validating the developed stochastic method, the statistics of the siltation results obtained via the stochastic method were compared with the siltation results observed in the SHP reduced model. It is noteworthy that in the physical model the result was available for two periods: 2008 to 2012, which was obtained by the authors of this article, and the period from 2013 to 2017, obtained by Teixeira et al (2020).…”
Section: Methodology Summarymentioning
confidence: 67%
See 4 more Smart Citations
“…Aiming at validating the developed stochastic method, the statistics of the siltation results obtained via the stochastic method were compared with the siltation results observed in the SHP reduced model. It is noteworthy that in the physical model the result was available for two periods: 2008 to 2012, which was obtained by the authors of this article, and the period from 2013 to 2017, obtained by Teixeira et al (2020).…”
Section: Methodology Summarymentioning
confidence: 67%
“…Since it was verified that the AR(1) model adjusted well to the data, each "Q" value of the 1000 series generated for the SHP was multiplied by the "K" factor, which was obtained randomly from a Normal distribution, as explained in the methodology . This was necessary to convert the annual flows (Q) to average flows of the maximum periods (Q MM ), since it is these flows that causes sediment transport in the SHP reservoir, as observed by Teixeira et al (2020). It should be noted that the statistical tests applied, at 5% significance, showed that the data set containing the "K" factor (Figure 4) is homogeneous, independent, random and stationary.…”
Section: Stochastic Modeling: Generation Of Synthetic Series Of Hydro...mentioning
confidence: 98%
See 3 more Smart Citations